MOTIVATION IN SPORTING ACTIVITIES: ANALYSIS OF THE SCHOOLS OF PHYSICAL EDUCATION IN HIGH SCHOOL IN A PUBLIC SCHOOL OF WEST CENTRAL MINEIRO (Fiep Bulletin - online, 2020)
This study aimed to evaluate the motivation of high school students of a public school in the Midwest region of Minas Gerais, making a comparative analysis between students who "do" and those who "do not" sport activities in class of Physical Education. The participants of this research were 43 students, at the 1st and 2nd level of high school, with an average age of 15.81, where 21 (10 male and 11 female) are students who “do ” physical education sports classes often and 22 (12 male and 10 female) students who“ do not” physical education sports classes. Three instruments were used, the Sport Motivation Scale, which is composed of 28 items that are equally divided into seven dimensions of Intrinsic and Extrinsic Motivation, the Physical Activity Practice Motivation Scale, an instrument that contains 54 items; related to the reasons why the individual practices physical exercises and the Personality Factorial Inventory. For data treatment, a descriptive statistics (mean and standard deviation) was used. The results indicate that students who "do" sports activities frequently in Physical Education classes are more motivated (intrinsically and extrinsically) than students who "do not". We conclude that although students who “do” are more motivated than students who “do not”, students in general analysis have a moderate and high motivational profile that are potentially favorable so that Physical Education works can be structured that all effectively do the activities thus avoiding dropout in class. The aim of this paper is to contribute to the Physical Education teachers to develop in their classes, psychological strategies of motivation for sports practice.
Keywords: School Physical Education. Motivational Assessment. Sports Practices